Development of e-modules based on science literacy and Islamic values in ecosystem materials - Achmad Ali Fikri; Alfiyatul Rahmaniyyah (Research and Development in Education (RaDEn), 2023)
In the reality of general education, many teachers still use conventional teaching materials, namely teaching materials that are ready, can be purchased instantly, without having to plan, prepare and organize themselves. The purpose of this study was to determine the feasibility of developing e-modules based on scientific literacy and Islamic value in biology learning on ecosystem material for class X IPA at MA Mu'allimat NU Kudus. This Study use he 4-D research model which was modified into a 3-D development model by eliminating the disseminate stage so that the research was only carried out until the develop stage. The subjects of the product trial totaling 42 students. Data collection techniques with validation instruments by material expert lecturers, media expert lecturers, practitioners, and the student response questionnaire. The results of the material expert validation were obtained "very feasible", the results of the media expert validation were obtained "very feasible", and the results of the biology teacher's validation were also obtained "very feasible". Student response to the e-module was obtained "very feasible". So that this research succeeded in developing e-modules and is very suitable for use as teaching materials. The results of this study are expected to answer the need for media in learning activities, besides that it is also able to motivate teachers to develop more in class.